2022
DOI: 10.1371/journal.pone.0261998
|View full text |Cite
|
Sign up to set email alerts
|

Age-friendly neighbourhoods and physical activity of older Surinamese individuals in Rotterdam, the Netherlands

Abstract: Background Age-friendly neighbourhoods seem to promote physical activity among older individuals. Physical activity is especially important for chronically ill individuals. In the Netherlands, older Surinamese individuals are more likely to have chronic diseases than are their native Dutch counterparts. This study examined relationships of neighbourhood characteristics with physical activity among older Surinamese individuals in Rotterdam, the Netherlands. Methods Of 2749 potential participants, 697 (25%) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 130 publications
(126 reference statements)
0
18
0
Order By: Relevance
“…Less than half of participants in our study met the PA guidelines of ≥ 5 days per week at least 30 min physically active. A recent study among older Surinamese adults showed that neighbourhood characteristics have an important role in supporting older Surinamese adults in engaging an active lifestyle [ 52 ]. Thus, policy makers should promote neighbourhood interventions that promote/support PA among the older Surinamese population, which might also be beneficial for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Less than half of participants in our study met the PA guidelines of ≥ 5 days per week at least 30 min physically active. A recent study among older Surinamese adults showed that neighbourhood characteristics have an important role in supporting older Surinamese adults in engaging an active lifestyle [ 52 ]. Thus, policy makers should promote neighbourhood interventions that promote/support PA among the older Surinamese population, which might also be beneficial for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Validated tool for AFS environment assessment 55,73 and community level indicators for AFS develped 53 …”
Section: Resultsmentioning
confidence: 99%
“…Individual well‐being 53 and social support 38 positively impacted by AFS neighborhood characteristics…”
Section: Resultsmentioning
confidence: 99%
“…These active behavioral patterns are in uenced by the features that are organized and con gured in the city spaces (Ulijaszek, 2018). The role of the physical environment in the city and neighborhood in supporting or hindering different levels of physical activity of citizens has received a lot of attention in the past few decades (Wali et al, 2022) (Jagroep et al, 2022) (Duncan et al, 2021) (King et al, 2019) (Kärmeniemi et al, 2018) (Barnett et al, 2017) (Cerin et al, 2014) (Handy et al, 2002). According to the ecological model of health behavior, physical activity in older adults is in uenced by their surrounding environment, which, in turn, is determined by personal, interpersonal, and physical environmental factors (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to the ecological model of health behavior, physical activity in older adults is in uenced by their surrounding environment, which, in turn, is determined by personal, interpersonal, and physical environmental factors (Chen et al, 2019). Past research also shows that the neighborhood plays an important role in supporting the physical activity lifestyle of the older adults (Jagroep et al, 2022). An active lifestyle in old age has a great impact on general health (Paillard-Borg et al, 2012) in that it can help reduce the risk of chronic diseases, improve the quality of life of the older adults (Chodzko-Zajko, 2014), promote mental health (Teychenne, et al, 2020), function as a protective factor to delay dementia at old age (Paillard-Borg et al, 2012), cause happiness and satisfaction in life (An et al, 2020), and improve sleep quality and reduce depression (Kadariya et al, 2019).…”
Section: Introductionmentioning
confidence: 99%